High aspect ratio microfilling for MEMS using metal nanopowder / Fatin Syazana Jamaludin - Fatin Syazana , Jamaludin (2013)
High aspect ratio microstructures (HARMS) are sought in MEMS devices, as they fulfil several criteria such as low driving voltage, increased structural rigidity, higher sensitivity in sensor systems, bigger displacement and greater actuation force in actuator applications, and larger magnetic forces for magnetic MEMS. However, the fabrication of HARMS requires advanced equipment and complicated fabrication procedures, which increase the production cost. Thus, the objective of this project is to explore a fabrication method to produce HARMS, which considers the best compromise between simple production techniques and high device performance. In this research, focused ion beam (FIB) milling was introduced to fabricate high aspect ratio microholes. Nickel nanopowder was chosen as a candidate of metal structural filling for HARMS due to its intrinsic net shaping characteristics and its superior mechanical properties, such as high fracture toughness. Microholes (2.0μm x 17.5μm) with a maximum aspect ratio 8 were achieved using the FIB direct milling technique. The parameters used to obtain this aspect ratio were 500pA for beam current and 100μm for initial milling depth. Milling was done using a beam current of 500pA, which formed the most precise microhole structure with low milling time and an aspect ratio close to 1, compared to the other holes. The aspect ratio of microholes increased with increase of the initial milling depth, Di. The actual depth, Df gained was 17.5μm at Di = 100μm, which is five times less than the initial milling depth. Although FIB milling is less useful in mass production, it is an excellent choice for producing highly precise microholes. However, it is limited by the effects of amorphisation and re-deposition. For the filling process, two different methods were used; magnetic assembly and ultrasonic dispersion followed by annealing at 500°C. The magnetic assembly technique provided better filling behaviour compared to the ultrasonic dispersion method due to the occurrence of agglomeration at the entire sidewall using the magnetic assembly technique. This agglomeration was induced by the magnetic field, which attracted the ferromagnetic nickel into the holes. The filling structure formed after annealing at 900°C is of higher quality with fewer voids than the filling structure formed at 500°C. Only small agglomerations were formed at the entire sidewall, no voids occurred and a higher average thickness of filling structure of 526nm was achieved. Furthermore, the annealing process created bonding between the nickel nanopowder and silicon substrate thus forming a nickel silicide (NiSi) layer. The composition of nickel was higher at 900°C (14.78%) rather than 500°C (4.36%), where in the former case; more nickel nanopowder diffused into the silicon and formed two phases of nickel silicide layer, NiSi and NiSi2. Although the agglomeration occurred at the sidewall of holes, a good formation of microfilling was achieved without cavitations. Thus, from this research, the magnetic assembly technique with annealing temperature of 900°C provides optimal conditions of microfilling using Ni nanopowder.